Anxious and Hostile: Consequences of Anxious Adult Attachment in Predicting Male-Perpetrated Sexual Assault. Issue 13 (July 2018) - Barbaro, Nicole; Parkhill, Michele R.; Nguyen, David
Attachment theory has increasingly been utilized to understand the etiology of sexual violence, and anxious attachment appears to be especially informative in this domain. We investigate the influence of general anxious attachment and specific anxious attachment on hostile masculine attitudes to predict male-perpetrated sexual assault. We hypothesize that hostile masculinity will mediate the relationship between general anxious attachment style and sexual assault perpetration (Hypothesis 1) and the relationship between specific anxious attachment to the assaulted woman and sexual assault perpetration (Hypothesis 2). Men ( N = 193) completed the Sexual Experiences Survey (SES) to determine sexual assault history and completed measures of general attachment style, specific attachment to the woman involved in the sexual activity, and measures of hostile masculine attitudes. Results support the hypothesized mediation models, such that general anxious attachment and specific anxious attachment are significantly associated with hostile masculinity, which in turn, predicts the likelihood of male-perpetrated sexual assault. The findings suggest that the unique characteristics of anxious attachment may escalate into hostile masculinity, which then increases the likelihood of sexual assault perpetration. This research is the first to investigate attachment bonds to the woman involved in the sexual activity and likelihood of sexual assault perpetration against the same woman.